Sosialisasi dan Praktek Tentang PPC ( Pencegahan dan Perawatan Cidera Olahraga ) dan Massage Olahraga (International Forum of Researchers and Lecturers, 2024)
The MBKM KKN group at the University of Riau, Kuala Gasib village, Koto Gasib District, Siak Regency is one of the programs of the Education Department where in this MBKM KKN we are students at the University of Riau majoring in Sports Education. This MBKM KKN was carried out for 41 days from July 15 to August 24 2024. In this MBKM KKN we took the title namely Together with the Community of Kampung Kuala Gasib Dare to Live Healthy.